Tentative Identification of Etazene (Etodesnitazene) Metabolites in Rat Serum and Urine by Gas Chromatography–Mass Spectrometry and Accurate Mass Liquid Chromatography–Mass Spectrometry. Issue 9 (5th January 2022) - Grigoryev, Andrej; Kavanagh, Pierce; Dowling, Geraldine; Rodin, Igor
Abstract: 2-Benzylbenzimidazole derivatives comprise a small but forensically significant group of synthetic opioids. In humans, the metabolism of some members of this group is extensive, with little or none of the parent compound remaining. The recent detection of the 2-benzylbenzimidazole derivative, etazene (etodesnitazene), in products seized in Russia required the detection of its metabolites in biofluids for forensic toxicology purposes. Using gas chromatography--mass spectrometry (GC–MS) and high resolution accurate mass (HRAM) liquid chromatography–mass spectrometry (LC–MS), eight etazene metabolites were found in the urine and serum of rats. These were tentatively identified as products of N-deethylation, O-deethylation, hydroxylation or N-oxidation of benzimidazole moiety and combinations of these processes. The parent substance and its O-deethylated metabolite prevailed in rat serum, while in urine, the level of etazene was low compared to N, O-deethylated and N-deethylated with hydroxylation metabolites. Glucuronidated, sulfonated and glutathionated forms were not found. Taking into account reports on the study of the metabolism of other 2-benzylbenzimidazole derivatives in humans, it may be concluded that the mono-deethylated and mono-hydroxylated metabolites are suitable as target analytes in urine.